Markers of assimilation of problematic experiences in dementia within the LivDem project. (May 2017) - Cheston, Richard; Gatting, Lauren; Marshall, Ann; Spreadbury, John H; Coleman, Peter
This study aimed to determine whether the Markers of Assimilation of Problematic Experiences in Dementia scale (MAPED) can be used to identify whether the way in which participants talk about dementia changed during the group. All eight sessions of a LivDem group, which were attended by participants were recorded and transcribed. An initial analysis identified 160 extracts, which were then rated using the MAPED system. Inter-rater reliability was 61% and following a resolution meeting, 35 extracts were discarded, leaving 125 extracts with an agreed marker code. All of the participants were identified as producing a speech marker relating to dementia, and these varied between 0 (warding off) to 6 (problem solution). Examples of these markers are provided. The proportion of emergence markers (indicating the initial stages of assimilation) compared to later markers changed significantly between the first four sessions and the final sessions. This difference was still significant even when the markers produced by the most verbal participant, Graham, were excluded. The use of process measures within psychotherapy complements more conventional outcome measures and has both theoretical and clinical implications.